2023
DOI: 10.3390/molecules28062785
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of a Natural Biosorbent for Removing Methylene Blue Dye from Aqueous Solution

Abstract: T he current study reports the use of zeolite prepared from a kaolin composite via physical mixing with different ratios from fiber of palm tree (Zeo-FPT) as a sustainable solid sorbent for the removal of methylene blue (MB) dye from aqueous solutions. The prepared biosorbent was fully characterized using XRD, TGA, SEM, and FTIR. The impacts of various analytical parameters, for example, contact time, dosage, MB dye concentration, and the pH of the solution, on the dye adsorption process were determined. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It can be observed that the dye filtration effect was almost constant under these three different water conditions. Therefore, POMOF1/PAN NFM can filter organic dyes under various concentrations and different water quality conditions, indicating its substantial practical applicability [46]. Additionally, Table S3 lists some information regarding the removal rates of the three cationic dyes, which includes the utilization of membranes prepared using different polymers or composite membranes synthesized through doping different MOFs or inorganics with PAN as the substrate.…”
Section: Adsorption Kinetics and Isothermsmentioning
confidence: 99%
“…It can be observed that the dye filtration effect was almost constant under these three different water conditions. Therefore, POMOF1/PAN NFM can filter organic dyes under various concentrations and different water quality conditions, indicating its substantial practical applicability [46]. Additionally, Table S3 lists some information regarding the removal rates of the three cationic dyes, which includes the utilization of membranes prepared using different polymers or composite membranes synthesized through doping different MOFs or inorganics with PAN as the substrate.…”
Section: Adsorption Kinetics and Isothermsmentioning
confidence: 99%
“…Mycotoxin sorption studies of the clays, charcoals, and biochars were carried out using a Max Q4450 incubating shaker with the rpm set at 60 and the temperature at 37 • C. Various concentrations (0.1 ppm and 1 ppm) of single evaluations of aflatoxin B1, ochratoxin A, and zearalenone were incubated with biochar (1 mg) dispersed in 1 mL solutions (pH 2.0, 100 mM sodium phosphate buffer, and pH 5.5, 100 mM sodium phosphate buffer) in 1.8 mL vials using variations of previously published procedures [5,20,[27][28][29][30]. Following the two hours incubation, the samples were centrifuged for ten min at 3800 rpm.…”
Section: Equilibrium Sorption Assaysmentioning
confidence: 99%